A black hole detected in the young massive LMC cluster NGC 1850. Issue 2 (11th November 2021) - Saracino, S; Kamann, S; Guarcello, M G; Usher, C; Bastian, N; Cabrera-Ziri, I; Gieles, M; Dreizler, S; Da Costa, G S; Husser, T-O; Hénault-Brunet, V
ABSTRACT: We report on the detection of a black hole (NGC 1850 BH1) in the ∼100-Myr-old massive cluster NGC 1850 in the Large Magellanic Cloud. It is in a binary system with a main-sequence turn-off star (4.9 ± 0.4 M⊙ ), which is starting to fill its Roche lobe and is becoming distorted. Using 17 epochs of Very Large Telescope/Multi-Unit Spectroscopic Explorer observations, we detected radial velocity variations exceeding 300 km s −1 associated with the target star, linked to the ellipsoidal variations measured by the fourth phase of the Optical Gravitational Lensing Experiment in the optical bands. Under the assumption of a semidetached system, the simultaneous modelling of radial velocity and light curves constrains the orbital inclination of the binary to 38° ± 2°, resulting in a true mass of the unseen companion of $11.1_{-2.4}^{+2.1}\, {\rm M}_{\odot }$ . This represents the first direct dynamical detection of a black hole in a young massive cluster, opening up the possibility of studying the initial mass function and the early dynamical evolution of such compact objects in high-density environments.